2001
DOI: 10.1046/j.1523-1755.2001.0590041498.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-related glomerulopathy: An emerging epidemic

Abstract: ORG is distinct from idiopathic FSGS, with a lower incidence of nephrotic syndrome, more indolent course, consistent presence of glomerulomegaly, and milder foot process fusion. The ten-fold increase in incidence over 15 years suggests a newly emerging epidemic. Heightened physician awareness of this entity is needed to ensure accurate diagnosis and appropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
905
8
33

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,127 publications
(979 citation statements)
references
References 42 publications
33
905
8
33
Order By: Relevance
“…However, the significant correlation between weight loss and serum creatinine and urinary protein excretion indicates that weight loss, at least, contributes greatly to the improvement. Several studies showed that obese patients could develop proteinuria and progressive loss of renal function, 17,18 and weight loss improved them. 8,19 The proposed mechanisms by which obesity increased renal risk include increasing GFR, 20 focal segmental glomerulosclerosis, 21 activation of the rennin-angiotensin system, 8 and adipocyte-derived cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…However, the significant correlation between weight loss and serum creatinine and urinary protein excretion indicates that weight loss, at least, contributes greatly to the improvement. Several studies showed that obese patients could develop proteinuria and progressive loss of renal function, 17,18 and weight loss improved them. 8,19 The proposed mechanisms by which obesity increased renal risk include increasing GFR, 20 focal segmental glomerulosclerosis, 21 activation of the rennin-angiotensin system, 8 and adipocyte-derived cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Increased numbers of interstitial cells and an increase in material rich in lipids and proteoglycans compresses the renal parenchyma toward the pole of the kidney resulting in the formation of round-shaped, enlarged kidneys in obese subjects. 29,30 Renal compression affects both vascular (mainly the vasa recta) and tubular (the Henle's loops) elements causing activation of the RAS and increased sodium reabsorption.…”
Section: Structural Changes In the Kidneymentioning
confidence: 99%
“…There is also evidence that SNS response to hypoxia may affect the renal circulation in patients with obstructive sleep apnea, an abnormality often seen in the obese population. 4,30 Hyperfiltration as a result of heightened blood flow to the kidney is always present in obesity, long before glomerulopathy occurs. It is, therefore, the primary cause of gradual sclerosis of the glomeruli wall because of physical stress and eventually of a vicious circle in which nephrons are injured, sodium retention worsens and arterial pressure reaches higher values to maintain sodium balance.…”
Section: Structural Changes In the Kidneymentioning
confidence: 99%
“…These include ectopic lipid accumulation [42] and increased deposition of renal sinus fat [43,44], the development of glomerular hypertension and increased glomerular permeability caused by hyperfiltrationrelated glomerular filtration barrier injury [45], and ultimately the development of glomerulomegaly [46], and focal or segmental glomerulosclerosis [41] (Fig. 2).…”
Section: Mechanisms Of Action Underlying the Renal Effects Of Obesitymentioning
confidence: 99%